Living with torturers and other essays of intervention : Sri Lankan society, culture, and politics in perspective - Perera, Sasanka (Colombo : International Centre for Ethnic Studies, 1995)
Collection of essays focussing on causes that led to current political crisis in Sri Lanka.
Keywords: Violence -- Sri Lanka; Sri Lanka -- Politics and government -- 1978-; Sri Lanka -- Social conditions